1999
DOI: 10.1002/(sici)1097-0045(19991101)41:3<203::aid-pros8>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Androgen-independent expression ofhoxb-13 in the mouse prostate

Abstract: BACKGROUND Hox genes encode transcriptional regulatory proteins that are largely responsible for establishing the body plan of all metazoan organisms. A subset of Hox genes is expressed during the period of organogenesis and into adulthood. hoxb‐13 is a recently‐described member of the Hox gene family that is expressed in the spinal cord, hindgut, and urogenital sinus during embryogenesis. METHODS Northern blot and in situ hybridization analyses of hoxb‐13 expression in adult mouse tissues were performed. RESU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
91
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(101 citation statements)
references
References 25 publications
9
91
0
Order By: Relevance
“…HOXB13 methylation is associated with gene silencing Although abundant expression of HOXB13 in normal prostate and colorectal tissues of adult mouse and humans has been reported (Sreenath et al, 1999;Jung et al, 2004b), our reverse transcription-PCR (RT-PCR) analysis revealed that HOXB13 is also expressed in the normal human kidney, testis, uterus, placenta, and thymus in addition to the prostate (Figure 3a). To elucidate whether aberrant methylation of HOXB13 is associated with the loss of its expression in RCCs, we analysed the expression of HOXB13 in 15 RCC lines by RT-PCR that amplified the HOXB13 cDNA to plateau levels ( Figure 3b).…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…HOXB13 methylation is associated with gene silencing Although abundant expression of HOXB13 in normal prostate and colorectal tissues of adult mouse and humans has been reported (Sreenath et al, 1999;Jung et al, 2004b), our reverse transcription-PCR (RT-PCR) analysis revealed that HOXB13 is also expressed in the normal human kidney, testis, uterus, placenta, and thymus in addition to the prostate (Figure 3a). To elucidate whether aberrant methylation of HOXB13 is associated with the loss of its expression in RCCs, we analysed the expression of HOXB13 in 15 RCC lines by RT-PCR that amplified the HOXB13 cDNA to plateau levels ( Figure 3b).…”
Section: Resultsmentioning
confidence: 87%
“…A previous report showed that loss-of-function mutations in the murine Hoxb13 gene cause overgrowth of the secondary neural tube, the caudal spinal ganglia, and the caudal vertebrae, which are derived from the tail bud . Furthermore, Hoxb13 is also expressed in the prostate gland of the adult mouse (Sreenath et al, 1999). In addition, mice lacking Hoxb13 showed hypoplasia of the ventral prostate duct tips and did not produce secretory proteins, suggesting that Hoxb13 is required for the normal differentiation of the ventral prostate .…”
Section: Discussionmentioning
confidence: 99%
“…In the prostate gland, the posterior Hox13 genes are involved in positional identity and differentiation. Of these, Hoxb13 is expressed in the epithelium where it plays a specific role in differentiation (62,63). In the rat prostate, Hoxb13 epithelial expression increased postnatally and was expressed at the highest levels in the ventral lobe (38).…”
Section: Molecular Pathways For Developmental Estrogenization Of the mentioning
confidence: 99%
“…Hoxb13 is limitedly expressed in the caudal extent of the spinal cord, tail bud and urogenital sinus (Zeltser et al, 1996;Sreenath et al, 1999). In the adult mouse, Hoxb13 is confined to the epithelial cells of the prostate and distal colon and rectum (Zeltser et al, 1996;Sreenath et al, 1999).…”
mentioning
confidence: 99%
“…Hoxb13 is limitedly expressed in the caudal extent of the spinal cord, tail bud and urogenital sinus (Zeltser et al, 1996;Sreenath et al, 1999). In the adult mouse, Hoxb13 is confined to the epithelial cells of the prostate and distal colon and rectum (Zeltser et al, 1996;Sreenath et al, 1999). Tissue-specific expression of HOXB13 is also well reported in human (Aarnisalo et al, 1998;Edwards et al, 2005;Hood et al, 2004;Jung et al, 2004b;Takahashi et al, 2004).…”
mentioning
confidence: 99%